2022
DOI: 10.1002/leap.1489
|View full text |Cite
|
Sign up to set email alerts
|

Authors publishing repeatedly in predatory journals: An analysis of Scopus articles

Abstract: Scholars engage with so-called predatory or questionable journals for many different reasons. Among the contributing factors are monetary payoffs and the possibility of fast track faculty positions or promotion. It has been claimed that fast tracking promotion by using predatory publication outlets is an increasing problem. This study analyses the authors publishing in predatory journals with a focus on authors repeatedly publishing in predatory journals. In this study, a set of so-called predatory journals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This study, however reported about 37% of the respondents considering traditional publishing to be less likely to be predatory (Table 5). Charging authors without providing a service in return is the predatory journals business model, 18 and there is potential for education about identifying predatory publishing more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This study, however reported about 37% of the respondents considering traditional publishing to be less likely to be predatory (Table 5). Charging authors without providing a service in return is the predatory journals business model, 18 and there is potential for education about identifying predatory publishing more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Beall's list also contains potentially predatory publishers. While the list may have its shortcomings and debate is ongoing concerning its use, many studies have used it to define and classify predatory journals (see, for instance, Bagues et al, 2019; Frandsen, 2022; Marina & Sterligov, 2021; Macháček & Srholec, 2022; McCutcheon et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Newcomers to academe from the Global South may have been in the eye of the predatory storm, but the socio-economic and geographical dispersion of the problem turned out to be much wider, extending to academics from high-and upper-middle-income countries (IAP, 2022;Elliott et al, 2022;Moher et al, 2017; Segado-Boj; Martín-Quevedo; Prieto Gutiérrez, 2022), as well as to the senior and experienced among them (Alecci, 2018;Elliott et al, 2022). Indeed, researchers from Italy (Bagues; Sylos-Labini; Zinovyeva, 2017), Belgium (Eykens et al, 2019) and Denmark (Shaghaei et al, 2018) were found to have published in questionable journals, as did senior academics (Alrawadieh, 2018;Eykens et al, 2019;Frandsen, 2022;Perlin;Imasato;Borenstein, 2018;Pyne, 2017;Shaghaei et al, 2018;Wallace;Perri, 2018). Perhaps most tellingly, over 5000 researchers from German universities, institutes and federal agencies, inclusive of prominent professors, even a Nobel laureate, have also been found to have published articles in predatory journals with no peer review processes (NDR, 2018;Offord, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%